(untitled) (Indonesian Health Justice Review, 2024)
Mental health care in Indonesia remains a critical yet underfunded area of the healthcare system, with significant gaps in accessibility, quality, and social acceptance. This paper examines the role of mental health in achieving social justice and explores the barriers faced by individuals seeking mental health care, particularly in rural and marginalized communities. Through a mixed-methods approach, the study evaluates national mental health policies, healthcare infrastructure, and interviews with mental health professionals and patients. Findings reveal that mental health services in Indonesia are often stigmatized, under-resourced, and concentrated in urban areas, leaving rural populations with minimal support. Moreover, societal stigma surrounding mental health further exacerbates delays in seeking treatment. The research calls for policy changes to improve mental health care access, increase public awareness, and reduce stigma. The paper advocates for the integration of mental health services into primary care settings, increased funding for mental health infrastructure, and training for healthcare workers to better address mental health issues in a socially just manner.